Assessment for Evaluation of Local Roads Based on Infrastructure Data and Budget Allocation - Meriana, Desi; Subagio, Bambang S.; Najid, . (Civil Engineering Journal, 2025)
Technical criteria are one of the determining factors in calculating the technical index amount of the allocation budget for road infrastructure. The technical criteria include pavement deterioration, bridge condition, road performance, local budget allocation for road capital expenditure, allocation of local budget government for routine maintenance of roads, e-monitoring reporting, and SHP map reporting. Evaluation is required to determine the influence of each of these criteria and highlight the importance of comprehensive and continuous data testing to provide an overview of road infrastructure data and budget allocations. This study aims to analyze the influence of each technical criterion based on infrastructure data and the allocation of funding for local road maintenance in Indonesia. Two regression methods, Multiple Linear Regression with Dummy (MLRD) and Binary Logistic Regression (BLR), were used to identify and evaluate each variable and the potential of the resulting criteria. The results show that pavement deterioration (PD) and road performance (RP) are the criteria that significantly influence the assessment of infrastructure data and are the best models. This finding highlights the need for comprehensive data testing to provide an accurate overview of local road infrastructure from the data submitted by local governments to the central government. Doi: 10.28991/CEJ-2025-011-01-04 Full Text: PDF